First Evaluation of the Role of Salp Fecal Pellets on Iron Biogeochemistry - Cabanes, Damien J. E.; Norman, Louiza; Santos-Echeandía, Juan; Iversen, Morten H.; Trimborn, Scarlett; Laglera, Luis M.; Hassler, Christel S. (Frontiers in Marine Science, 2017)
Planktonic grazers such as salps may have a dominant role in iron (Fe) cycling in surface waters of the Southern Ocean (SO). Salps have high ingestion rates and egest large, fast sinking fecal pellets (FPs) that potentially contribute to the vertical flux of carbon. In this study, we determined the impact of FPs from Salpa thompsoni, the most abundant salp in the SO, on Fe biogeochemistry. During the Polarstern expedition ANT-XXVII/3, salps were sampled from a large diatom bloom area in the Atlantic sector of the SO. Extensive work on carbon export and salp FPs export at the sampling location had shown that salps were a minor component of zooplankton and were responsible for only a 0.2% consumption of the daily primary production. Furthermore, at 100 m, export efficiency of salp FPs was ~2-3 fold higher than that of the bulk of sinking particulate organic carbon (POC). After collection, salps were maintained in 200 µm screened seawater and their FPs were collected for further experiments. To investigate whether the FPs release Fe and/or Fe-binding ligands into the filtered seawater (FSW) under different experimental conditions, they were either incubated in the dark or under full sunlight at in situ temperatures for 24h, or placed into the dark after a freeze/thaw treatment. We observed that none of the treatments caused release of dissolved Fe (dFe) or strong Fe ligands from the salp FPs. However, humic-substance like (HS-like) compounds, weak Fe ligands, were released at a rate of 8.2 ± 4.7 µg HS-like FP-1 d-1. Although the Fe content per salp FP was high at 0.33 ± 0.02 nmol dFe FP-1, the small contribution of salps to the zooplankton pool resulted in an estimated dFe export flux of 11.3 nmol Fe m-2 d-1 at 300 m. Since salp FPs showed an export efficiency at 100 m well above that shown by the bulk of sinking POC, our results suggest that in those areas of the SO where salps play a major role in the grazing of primary production, they could be actively contributing to the depletion of the dFe pool in surface water.